A case of trichilemmal carcinoma following lung transplantation - Jie ZHAO; Daxing CAI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
A case of Trichilemmal carcinoma is reported. A 71-year-old man had undergone left lung transplantation 4 years ago. An asymptomatic light red mass in green- bean size appeared on the left temporal area 3 years ago, without any treatments. The skin lesion grew rapidly since half a year ago. Physical examination showed a reddish plaque sized about 2.5 cm×2.0 cm on the left temporal area with a slightly rough surface. Histopathology showed that the infiltrative tumor mass was involved in the sebaceous glands, sebaceous ducts, and hair follicles. Atypical cells and pathological mitosis were evident. Diagnosis: Trichilemmal carcinoma. Extensive surgical excision and rhomboplasty were performed. No recurrence was observed during follow up.